The Radio Australia Aerial Matrix Switch - Moorhead, Simon (Journal of Telecommunications and the Digital Economy, 2017)
Two papers from 1963 describing the design and construction of the new aerial matrix switch at Radio Australia Shepparton and the ingenuity required to conceive and deploy a world-first solution.